A Caged World: A critical analysis of Queer oppression in Wilde’s The Picture of Dorian Gray, Statovci’s Crossing and Baldwin’s Giovanni’s Room - Kabir, Silvia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.